WORKING CONDITIONS AS CAUSATIVE FACTOR FOR HIGH TURNOVER AMONG ICT STAFF IN FEDERAL UNIVERSITIES IN SOUH-WEST, NIGERIA - ODUSANYA, ANIKE. T; ANDU-ANIMASHAUN, MODINAT TANIMOSE (Sokoto Educational Review, 2025)
This research examined the relationship between working conditions and high turnover among ICT professionals in federal universities in South-West Nigeria. Guided by two research questions and two hypotheses, the study employed a descriptive survey approach to explore the impact of various factors on turnover rates. The population comprised all Information and Communication Technology (ICT) personnel employed in South-West Federal universities. A multi-stage sampling procedure selected 48 participants. Data was collected using a self-developed, structured instrument named the Working Conditions and Manpower Turnover Questionnaire (WCMTQ), which includes 10 items rated on a 4-point modified Likert scale, and has received favorable evaluations. The instrument was validated by measurement and assessment experts, and a pilot test yielded a reliability coefficient of 0.78. Descriptive statistics, including frequency counts and percentages, were used for demographic analysis, while means were computed for research questions. Hypotheses were tested using Chi-square statistics, with analyses conducted using the Statistical Package for the Social Sciences (SPSS).